Utility of incorporating next-generation sequencing (NGS) in an Asian non-small cell lung cancer (NSCLC) population: Incremental yield of actionable alterations and cost-effectiveness analysis. (January 2020) - Tan, Aaron C.; Lai, Gillianne G.Y.; Tan, Gek San; Poon, Shou Yu; Doble, Brett; Lim, Tse Hui; Aung, Zaw Win; Takano, Angela; Tan, Wan Ling; Ang, Mei-Kim; Tan, Bien Soo; Devanand, Anantham; et al.
Highlights: Upfront NGS is feasible and cost-effective in an EGFR mutant predominant population. Characterizing the wider genomic profile may yield important information. There was a high proportion with targetable alterations in the PD-L1 > 50 % subgroup. Abstract: Objectives: There is an expanding list of therapeutically relevant biomarkers for non-small cell lung cancer (NSCLC), and molecular profiling at diagnosis is paramount. Tissue attrition in scaling traditional single biomarker assays from small biopsies is an increasingly encountered problem. We sought to compare the performance of targeted next-generation sequencing (NGS) panels with traditional assays and correlate the mutational landscape with PD-L1 status in Singaporean patients. Materials and methods: We identified consecutive patients diagnosed between Jan 2016 to Sep 2017 with residual tissue after standard molecular testing. Tissue samples were tested using a targeted NGS panel for DNA alterations (29 selected genes including BRAF, EGFR, ERBB2 and TP53 ) and an RNA fusion panel ( ALK, ROS1 and RET ). PD-L1 immunohistochemistry was also performed. A cost-effectiveness analysis of NGS compared to standard molecular testing was conducted. Results: A total of 174 samples were evaluated: PD-L1 (n = 169), NGS DNA panel (n = 173) and RNA fusion (n = 119) testing. Median age was 68 years, 53 % were male, 58 % were never smokers, 85 % were Chinese, 66 % had stage IV disease and 95 % had adenocarcinoma histology. In patients profiled with NGS on DNA, EGFR (56 %), KRAS (14 %), BRAF (2 %) and ERBB2 (1 %) mutations were found. RNA fusion testing revealed fusions in ALK (6 %), RET (3 %) and ROS1 (1 %). Cost-effectiveness analysis demonstrated that compared to sequential testing in EGFR negative patients, upfront NGS testing would result in an additional 1 % of patients with actionable alterations for targeted therapy being identified without significant increases in testing cost or turnaround time. Conclusions: This study demonstrates that even in an EGFR mutant predominant population, upfront NGS represents a feasible, cost-effective method of diagnostic molecular profiling compared with sequential testing strategies. Our results support the implementation of diagnostic NGS in non-squamous NSCLC in Asia to allow patients access to the most appropriate personalized therapy.